The analyze of LQ45 companies stock price in 2018-2020 - Samasta, Almira Santi; Lestari, Selvia Puji; Arsanda, Tiara Daffa (Nur Science Institute, 2021)
This study aims to analyze how much Earning Per Share, Debt to Equity Ratio, and Return on Equity to stock prices in companies indexed by the 2018-2020 LQ45 period. The population of this study is the LQ45 companies that are consistently indexed in 2018-2020. The sample of this study uses purposive sampling. The sample in this study was 35 companies. The type of data used is secondary data derived from a summary of financial statement records. The analysis technique uses multiple linear regression analysis. The results of the study found that Earning Per Share had an effect on stock prices, while Debt to Equity Ratio and Return On Equity had no effect on stock prices for LQ45 indexed companies consistently in the 2018-2020 period.